Radiological safety assessment for water treatment facility due to radon inhalation in Korea - Seung Beom Yoo; Shin Dong Lee; Jeong Woo Lee; Chang Hee Han; Kwang Pyo Kim (Nuclear Engineering and Technology, 2025)
Water treatment facilities are facilities that use groundwater to produce potable water. Groundwater can contain radon which is a naturally occurring radionuclide, and water treatment facility workers who directly handle groundwater are at risk of internal exposure from radon inhalation. The objective of this study is to assess the internal radiation dose from radon inhalation in water treatment facility workers in Korea. To achieve this, we analyzed work processes in 6 water treatment facilities in Korea, and main process areas were investigated through interviews with workers. The airborne radon concentration was measured in the main process areas using the RAD 7 and Raduet radon detector. Radon concentrations measured in the main process areas ranged from 16.6 to 756 Bq m−3, which is below the ICRP's reference level of 1,000 Bq m−3. The internal radiation dose due to radon inhalation ranged from 0.193 to 5.80 mSv y−1. This is about half of the ICRP's reference level of 10 mSv y−1 for radon inhalation. This study can be used as technical data for radiological safety management of NORM industries in Korea.